Targeting labour market programmes: results from a randomized experiment - Stefanie Behnke; Markus Frölich; Michael Lechner (Institute for the Study of Labor (IZA), 2007)
We evaluate a randomized experiment of a statistical support system developed to assist caseworkers in Swiss employment offices in choosing appropriate active labour market programmes for their unemployed clients. This statistical support system predicted the labour market outcome for each programme and thereby suggested an 'optimal' labour market programme for each unemployed person. The support system was piloted in several employment offices. In those pilot offices, half of the caseworkers used the system and the other half acted as control group. The allocation of the caseworkers to treatment and control group was random. The experiment was designed such that caseworkers retained full discretion about the choice of active labour market programmes, and the evaluation results showed that caseworkers largely ignored the statistical support system. This indicates that stronger incentives are needed for caseworkers to comply with statistical profiling and targeting systems.
Keywords: 330; Profiling; active labour market programmes; ALMP; statistical treatment rules; unemployment; public employment services; Arbeitsvermittlung; Computergestütztes Verfahren; Arbeitsmarktpolitik; Arbeitsverwaltung; Wirtschaftliche Effizienz; Schätzung; Schweiz